Severance packages - Fabien Postel-Vinay; Hélène Turon (Institute for the Study of Labor (IZA), 2011)
Job-to-job turnover provides a way for employers to escape statutory firing costs, as unprofitable workers may willfully quit their job on receiving an outside offer, thus sparing their incumbent employer the firing costs. Furthermore, employers can induce their unprofitable workers to accept outside job offers that they would otherwise reject by offering voluntary severance packages, which are less costly than the full statutory firing cost. We formalize those mechanisms within an extension of the Diamond-Mortensen-Pissarides (DMP) matching model that allows for employed job search and negotiation over severance packages. We find that, while essentially preserving most standard qualitative predictions of the DMP model without employed job search, our model explains why higher firing costs intensify job-to-job turnover at the expense of transitions out of unemployment. We further find that allowing for on-the-job search markedly changes the quantitative predictions of the DMP model regarding the impact of firing costs on unemployment and employment flows: ignoring on-the-job search leads one to strongly underestimate the negative impact of firing costs on unemployment.
urn:nbn:de:101:1-201110263632
Keywords: J33; J64; E24; 330; firing costs; on-the-job search; mutual consent; minimum wage; Abfindung; Kündigung; Kosten; Arbeitsmobilität; Arbeitsuche; Arbeitsnachfrage; Matching; Theorie